MANAJEMEN STRATEGI BLUE OCEAN KEPALA MADRASAH DALAM MEMBANGUN IKLIM LEMBAGA PENDIDIKAN - Muhammad Fauzi (Sekolah Tinggi Ilmu Tarbiyah Togo Ambarsari, 2025)
This study aims to analyze the application of the Blue Ocean Strategy in the management of madrasah principals and its role in building a conducive, creative, and competitive institutional climate. The research method employed is library research with a descriptive qualitative approach, involving the collection and analysis of literature such as books, journal articles, and previous studies relevant to the topic. Data were analyzed using content analysis techniques to identify the strategic steps of madrasah principals, their leadership roles in shaping the institutional climate, and the implications of implementing the Blue Ocean Strategy for improving educational quality. The findings indicate that madrasah principals can foster innovation through strategies of differentiation, elimination of obstacles, and the creation of new values relevant to the needs of educational institutions. In conclusion, the application of the Blue Ocean Strategy serves as an effective alternative management approach to enhance competitiveness, quality, and the unique characteristics of madrasahs without being trapped in conventional competition.